Flying Over Amazonian Waters: The Role of Rivers on the Distribution and Endemism Patterns of Neotropical Bats - Silva, Daiana C.; Oliveira, Hernani F. M.; Zangrandi, Priscilla L.; Domingos, Fabricius M. C. B. (Frontiers in Ecology and Evolution, 2022)
The Amazon comprises many of the largest rivers in the planet and also houses some of the richest bat communities in the world. Rivers are important geographic barriers for the dispersal and distribution of different taxa worldwide and, particularly in the Amazon region, they form the conceptual and empirical bases for the recognition of the so-called Areas of Endemism of terrestrial vertebrates. Despite the vast literature on the role of rivers on vertebrate community structure in the Amazon Forest, this process has never been investigated using a comprehensive dataset of Neotropical bat communities in the region. In this study, we aimed at: 1) evaluating the patterns of bat endemism across the Amazon Forest; 2) testing for the relationship between the distribution of bat species in the Amazon and the interfluve Areas of Endemism as currently recognized, and; 3) analyzing the importance of major Amazonian rivers in bat beta-diversity (turnover and nestedness) in the Amazon. Our results indicate that rivers are not major barriers for the current distribution of most bat species, and bat community composition breaks were divided into two clusters separating the east and west regions, and a third cluster in northern Amazon. In addition, there was no significant overlap among species distribution limits and the interfluve Areas of Endemism. Interestingly, the geographic patterns that we found for bat communities composition breaks highly resembles the one recovered using bird communities, suggesting that similar ecological and historical drivers might be acting to determine the distribution of flying vertebrates in the Amazon. Moreover, Amazonian bat distribution and endemism patterns were likely shaped by factors other than rivers, such as species interactions and the current environmental conditions. In conclusion, our results highlight the importance of modern analytical approaches to investigate large scale ecological patterns in the Neotropical region, and also challenge the widely recognized role of rivers on the determination of community structure and endemism patterns in the Amazon Forest, at least for bats.